STRATEGIC MANAGEMENT ACCOUNTING: DEFINITION AND TOOLS - Pylypiv, N.І.; Pіatnychuk, I.D. (The actual problems of regional economy development, 2017)
The article is dedicated to learning the essence of the definition of “strategic management accounting” in domestic and foreign literature. Strategic management accounting tools has been studied and identified constraints that affect its choice. The result of the study is that the understanding of strategic management accounting was formed by authors. The tools which are common for both traditional managerial accounting and strategic and the specific tools necessary for efficient implementation of strategic management accounting have been defined.